Совершенствование рабочих процессов гидротурбин на напоры 400 ÷ 800 м с применением новых конструктивных решений - Потетенко, Олег Васильевич; Яковлева, Людмила Константиновна; Самба Битори, Трезор Дес Бекет (НТУ "ХПИ", 2017)
На основе анализа повышенных потерь напора в подводящих органах гидротурбин РО 400 и РО 500 разработаны новые конструктивные решения, защищенные патентами Украины; исследованы характерные особенности рабочего процесса радиально-диагональных гидротурбин, проведено совершенствование рабочего процесса посредством применения многоэлементной комбинированной зависимости в системе регулирования, позволившей разработать гидротурбины радиально-диагонального типа на напоры вплоть до 800 ÷ 1000 м конкурентоспособные на внешнем рынке.

Based on the analysis of increased head losses in the turbine inlet Fr 400 and Fr 500, new design solutions protected by the patents of Ukraine have been developed; the characteristic features of the working process of Francis-Deriaz hydroturbines and the working process has been perfected through the application of a multi-element combined dependence in the control system that has made it possible to develop Francis-Deriaz hydraulic turbines for heads up to 800-1000 m competitive on the foreign market. The article presents new design solutions and improved the system of combinatorial dependence in the regulatory system allowing to expand the zone of reliable operation of hydroturbines by expenditure (capacities) and heads almost 2 times. Increase the average operating efficiency by 2 ÷ 7 %, significantly reduce the pulsation of velocities and pressures and thus increase the reliability and durability of operation of hydroelectric equipment.
Perfection of working processes of hydraulic turbines on heads 400 ÷ 800 m with application of new constructive decisions
Keywords: радиально-диагональные гидротурбины; высоконапорные турбины; гидроэнергетические ресурсы; производство электроэнергии; characteristic features of the working process; methodology; constructing universal characteristics; high-head Francis-Deriaz turbine